(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
This study examines the indirect effects of participation in budget preparation on managerial performance based on the impact of participation on relevant work-information availability as well as the impact of relevant work-information availability on managerial performance. Besides, the impact of interaction between participation and environmental uncertainty and the impact of interaction between information availability and environmental uncertainty on managerial performance will be studied. Using a Questionnaire, an empirical analysis of agriculture firms working on Syrian Coast was performed. The results show a positive impact of participation on relevant work-information availability and a positive impact of relevant work-information availability on managerial performance. On the other hands, no interaction effects are found. هدفت الدراسة إلى تحديد الأثر غير المباشر للمشاركة في إعداد الموازنة على الأداء الإداري؛ وذلك من خلال دراسة أثر المشاركة على توافر المعلومات, ثم دراسة أثر توافر المعلومات على الأداء الإداري. فضلاً عن دراسة أثر الحالة التفاعلية بين متغير المشاركة وحالة عدم التأكد البيئي على توافر المعلومات من جهة, وأثر الحالة التفاعلية بين توافر المعلومات وعدم التأكد البيئي على الأداء الإداري من جهة أخرى. لذلك تمَّ إجراء مسح ميداني باستخدام الإستبانة على منشآت القطاع الزراعي العامة العاملة في الساحل السوري, إذ تمَّ توزيع /72/ استبانة, استرجع منها /50/ استبانة. وقد أظهرت نتائج تحليل البيانات وجود تأثير إيجابي للمشاركة في إعداد الموازنة على توافر المعلومات, وتأثير إيجابي لتوافر المعلومات على الأداء الإداري. في حين لم تظهر النتائج أي تأثير للحالات التفاعلية.